(untitled) (Research, Society and Development, 2020)
The world is facing a pandemic caused by COVID-19, a disease caused by the new coronavirus SARS-CoV-2. This pandemic began in the municipal market in Wuhan, China, where several species of wild animals were commercialized and there were no adequate conditions for hygiene and food safety, which allowed this new virus to be transmitted from intermediate hosts to humans. SARS-CoV-2 is believed to have originated in bats and subsequently infected pangolins and, ultimately, humans. Therefore, there is a fundamental role of veterinary medicine in the prevention of emerging zoonotic diseases, such as COVID-19. Thus, the present literature review aims to discuss the roles of the veterinarian in coping with the COVID-19 pandemic. Scientific research bases were used and the following descriptors were used to search for the articles: COVID-19 OR SARS-CoV-2 OR Coronavirus AND One Health; COVID-19 OR SARS-CoV-2 OR Coronavirus AND Veterinary OR Medicine Veterinary. Current articles were selected, available in English and Portuguese. The emergence of SARS-CoV-2 shows the close relationship between human health, animal health, the condition of the ecosystem and people’s habits, which is the core concept of "One Health”. The veterinarian is an integral part of the global community of health professionals and plays a key role in the prevention and control of diseases, such as COVID-19. This professional has knowledge about other coronaviruses that affect animals and, therefore, can help in studies on the origin and transmission of SARS-CoV-2, as well as assist in the development of vaccines and antiviral drugs.